Civil defense, leadership and heuristics for the education of headquarters for emergency situations - Bereš, Paun J.; Bereš, Kristian P.; Cvetković, Sreten S. (Vojnotehnički glasnik / Military Technical Courier, 2015)
This paper presents solving heuristically conceived problems in the Civil Defence by making adequate decisions in an emergency and the state of emergency with a special emphasis on the application of the heuristic model of training emergency teams-headquarters and on the role of a leader as a factor of good leadership. It is intended for command and teaching staff of the Civil Defence: local authorities (mayors of districts, cities and municipalities - commanders) and the system of protection and rescue (the Sector for Emergency Situations).The heuristic approach to problem solving should enable command staff-leaders from the local to the national level to make adequate decisions in emergency situations after the proclamation of emergency and the state of emergency in a territory part or the whole territory of the Republic of Serbia - functioning of the civil defense and the third mission of the Army of Serbia, as well as to point out the necessity of coordination between the local and national level.